Constraints in phonological acquisition - Kager, René; Pater, Joe; Zonneveld, Wim (Cambridge University Press, 2004)
This outstanding volume presents a state-of-the-art overview of linguistic research into the acquisition of phonology, focusing on constraints in phonological acquisition. An introduction by the editors, providing a brief general tutorial on Optimality Theory, is followed by 10 chapters by well-known researchers in the field.